Enhancing Speaking Fluency Trough Content and Language Integrated Learning (CLIL): A Case Study of High School Students in Kerman Province (Global Journal of Human-Social Science, 2023)
This study examines the impact of content and language integrated learning CLIL a popular method for teaching English on the development of speaking skills among high school students Speaking skills are emphasized as crucial among the four language skills due to their effectiveness in communication The paper discusses the techniques employed by teachers in teaching speaking focusing on a sample of 100 intermediate students from a high school in the Yazd province To gather research data an Oxford Placement Test OPT was initially conducted to ensure homogeneity among the students followed by an IELTS test as a posttest for both groups to assess the influence of CLIL on speaking fluency Statistical analysis was performed using SPSS-26 software package The findings demonstrate the effectiveness of CLIL in enhancing learners speaking skills with a T-test used as the statistical test to answer the research question
Keywords: content and language integrated learning (CLIL); speaking skill; speaking fluency; language learning methodology